Workplace Spirituality and Psychological Empowerment on Job Satisfaction of Employees of PT Pagilaran Batang - Yunitarini, Siti; Yuliani, Ovi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to examine and analyze the influence of workplace spirituality and psychological empowerment on job satisfaction (Case Study on Employees of PT Pagilaran Batang). The type of research used in this research is causal research with data collection methods using questionnaire data and interviews. The object of this study were employees of PT Pagilaran with a total population of 855 employees, and the samples in this study were 90 employees. The analytical tool used in this study was multiple linear regression analysis and used a hypothesis test which was processed with the SPSS version 20 program. The results of this study indicate that workplace spirituality has a positive and not significant effect on job satisfaction, while psychological empowerment has a positive and significant effect on job satisfaction.